2018
DOI: 10.1093/eurpub/cky071
|View full text |Cite
|
Sign up to set email alerts
|

Who wants to cross borders in the EU for healthcare? An analysis of the Eurobarometer data in 2007 and 2014

Abstract: Cross-border patient mobility is more likely amongst the younger, the more educated and those from smaller countries. The directive does not seem to have promoted mobility at a large scale among the neediest citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…When quantified in a 2009 study of 200 hospitals across 8 countries foreign patients accounted for less than 1% of hospital admissions. [9] , [13] , [30] , [32] , [45] , [48] , [49] , [50] , [51] , [52] Many citizens living abroad chose to return home for healthcare and those who travelled for care tended to be younger patients. The most commonly treated conditions were heart disease and fractures.…”
Section: Challenges To Cross-border Healthcare In Europementioning
confidence: 99%
See 1 more Smart Citation
“…When quantified in a 2009 study of 200 hospitals across 8 countries foreign patients accounted for less than 1% of hospital admissions. [9] , [13] , [30] , [32] , [45] , [48] , [49] , [50] , [51] , [52] Many citizens living abroad chose to return home for healthcare and those who travelled for care tended to be younger patients. The most commonly treated conditions were heart disease and fractures.…”
Section: Challenges To Cross-border Healthcare In Europementioning
confidence: 99%
“…The most commonly treated conditions were heart disease and fractures. [9] , [51] , [52] , [53] In a 2018 report by the European Commission, member states reported that the number of patients who travelled for care annually in 2016 and 2017 was approximately 200 000 patients. In 2016 cross border healthcare cost the EU €65 000 000.…”
Section: Challenges To Cross-border Healthcare In Europementioning
confidence: 99%
“…The European (2011) directive on cross-border care allows EU citizens to access health care in any EU country. Using the Eurobarometer survey, Perelta-Santos and Perelman (2018) and Riedel (2016) have found that mobility within the EU has grown from 3.3% in 2007 to 4.6% in 2014. Thus, the EU patient directive (2011) has not altered the situation much.…”
Section: Travel For Basic Health Care: the Patient Approachmentioning
confidence: 99%
“…This directive has had a significant impact on the demand for cross‐border health care in the EU. Peralta‐Santos and Perelman () revealed that cross‐border patient mobility among EU countries increased by approximately 11% from 2007 to 2014, particularly for younger travellers and the relatively educated, and for smaller countries.…”
Section: Introductionmentioning
confidence: 99%